Application of Composite Soaking Solution in Fillet Storage and Caco-2 Cell Antioxidant Repair - Qing Shao; Zhongqiang Wang; Shumin Yi (Foods)
The inhibitory effect of compound soaking solution on the quality deterioration of fish fillets during storage and its repair effect on a cell oxidative damage model were investigated. Water holding capacity, cooking loss, thawing loss, thiobarbituric acid and sensory evaluation were used to verify that the composite soaking solution could improve the water loss and quality deterioration of fillets during frozen storage. At 180 d, water holding capacity was increased by 4.59% in the compound soaking solution group compared with the control. Cooking loss decreased by 6.47%, and thawing loss decreased by 13.06% (p < 0.05). The TBA value was reduced by 50%, and the degree of lipid oxidation was lower (p < 0.05). The results of the microstructure analysis showed that the tissue structure of fillets treated by the compound soaking solution was more orderly. The oxidative damage model of cells was achieved by soaking in treated fish fillet digestive juice, which inhibited the increase in reactive oxygen species content, maintained the integrity of the cell structure, and increased cell viability by 32.24% (p < 0.05). Compound soaking solution treatment could inhibit the quality deterioration of fish fillets during storage, and the digestive solution of fish fillets could improve the oxidative stress injury of Caco-2 cells induced by H2O2.